Performance Analysis of ECDSA Based SE-AODV Routing Protocol In VANETS - ., Deepak; ., Rajkumar (International Journal of Engineering and Technology, 2018)
Vehicular ad hoc networks is an emerging area for researchers to provide intelligent transportation system to the society. It is due to the wide area of applications of VANETs interest is developed among the people from different countries to be a part of it. Therefore many projects had been started and also presently working to implement VANETs in real world scenario. The main challenge in its implementation is to provide a secure mechanism against the various attacks and threats that have the capability to bring the network performance significantly down. In this paper to overcome different types of authentication based attacks in VANETs an ECDSA based secure routing protocol SE-AODV is proposed with security features incorporated in already existing AODV routing protocol. The performance of SE-AODV is evaluated and compared with original AODV and AODV with black hole attack (BH-AODV). The SE-AODV shows better performance with the parameters used for comparison with the variation in vehicle density, speed of vehicles and simulation time.Â